2010
DOI: 10.1037/a0020056
|View full text |Cite
|
Sign up to set email alerts
|

Community and school violence and risk reduction: Empirically supported prevention.

Abstract: The development, implementation, and research of two separate psychoeducational group programs are described. One of the programs, Project FREE (Family Rejuvenation, Education and Empowerment; developed by Paula T. McWhirter and her colleagues) focuses on mothers who have suffered domestic violence and their children as witnesses. The project includes parallel psychoeducational group sessions with battered mothers and a simultaneous psychoeducational group session with the children followed by a conjoint sessi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Likewise, Ohl et al (2013) confirmed the effectiveness of relationships for decreasing emotional symptoms. McWhirter and McWhirter (2010) garnered the results of the GOPEP intervention program (McWhirter et al, 1997), based on group sessions and on conjoint sessions, which entailed substantial collaboration between researchers and participants, and confirmed the effectiveness of the SOAR program (Student Optimistic Attitudes and Resilience Program) in reducing anxiety and depression. The FREE program, for its part, was effective in decreasing self-isolation among children and their mothers, survivors of domestic violence.Externalizing symptomatology: Four articles present improvements in aspects related to aggression and behavioral issues.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Likewise, Ohl et al (2013) confirmed the effectiveness of relationships for decreasing emotional symptoms. McWhirter and McWhirter (2010) garnered the results of the GOPEP intervention program (McWhirter et al, 1997), based on group sessions and on conjoint sessions, which entailed substantial collaboration between researchers and participants, and confirmed the effectiveness of the SOAR program (Student Optimistic Attitudes and Resilience Program) in reducing anxiety and depression. The FREE program, for its part, was effective in decreasing self-isolation among children and their mothers, survivors of domestic violence.Externalizing symptomatology: Four articles present improvements in aspects related to aggression and behavioral issues.…”
Section: Resultsmentioning
confidence: 94%
“…Ohl et al (2013) confirmed that the Pyramid project helped improve peer problems; however, they did not find positive effects on behavioral problems. McWhirter and McWhirter (2010) gathered evidence confirming the effectiveness of the FREE project in decreasing family conflict, and of the SCARE (Student-Created Aggression Replacement Education) program, one of the GOPEP intervention programs, in decreasing and managing aggression, anger, and violent behaviors. However, Cappella et al (2012) did not find significative differences in behavioral regulation as an effect of their BRIDGE intervention, although children identified as having behavioral problems benefitted more than their peers in the area of social relations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Psychotherapy focuses more on personality change, while psychological counseling stresses coping strategies as well as problem-solving (Gazda et al 2001). Prevention is an extension of the counseling approach that has proven to be particularly effective with children, teens, parenting groups, married couples, and with many health-based groups McWhirter and McWhirter 2010;Webster-Stratton and Herman 2008). A psychoeducational structure is frequently used.…”
Section: Fifth Stage Of Adjustment For Change: Skill-building That Lementioning
confidence: 99%